FUN STUDY BANGKITKAN SEMANGAT BELAJAR DAN KREATIVITAS ANAK DESA SUNGAI BERINGIN - Suroyo Suroyo; Rachmad Sumatra; Ade Mesrayani; Nikmatul Husnah Mukhlis; Nura Azizah; Mutia Pramadila; Tasya Riski Amelia; Nurlela Sari; Mahdatul Hilda (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Children have a different way of learning than adults. A child essentially does not realize that what they are doing while playing is something that their parents consider learning. Fun study is an activity carried out by children in a fun way and without coercion, but with a pattern that is expected to yield good developmental outcomes for the children. Fun study is also a way for children to channel their abundant energy and discover new things in an enjoyable and engaging manner. Adults may not realize the enjoyable research purposes that children engage in. When children play, they are developing their potential to create a strong foundation for facing future challenges. The KKN MBKM activities aim to provide references and education to parents in the village of Sungai Beringin to better understand the world of children, especially regarding the meaning of play and its essence. This is achieved through a review of various sources, including literature, research findings, and thoughts. This discovery can be used by parents in Sungai Beringin Village to improve their ability to support and design their children's learning, making the educational experience enjoyable and effectively achieving the pearls of learning.